The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/adsc.202200088
|View full text |Cite
|
Sign up to set email alerts
|

Combined Approach of Hypervalent Iodine Reagents and Transition Metals in Organic Reactions

Abstract: This review outlines the progress over recent years in the reactions involving combined approach of hypervalent iodine reagents and transition metals such as palladium, nickel, iridium, gold, rhodium, copper, iron, ruthenium, platinum, silver, zinc, rhenium and cobalt. This approach enables organic transformations complimentary to traditional manifolds. Hypervalent iodine reagents play a preeminent role in organic chemistry due to their versatile reactivity, heteroatom ligands and mild reaction conditions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 159 publications
0
6
0
Order By: Relevance
“…Over the last two decades, the combination of hypervalent iodine reagents with gold, 91 and other transition-metals has allowed the functionalization of a broad range of substrates. 21 For example, the Hashmi group reported a bimetallic gold–silver catalytic system for the synthesis of 3-alkynyl benzofurans from phenols and EBx reagents ( Scheme 21 ). 92 Mechanistic studies, suggested that a bimetallic Au–Ag catalyst promoted a tandem ortho C(sp 2 )–H alkynylation/oxyalkynylation reaction by leveraging the exceptional redox property and carbophilic π-acidity of gold.…”
Section: Transition-metal Mediated Alkynylation Reactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last two decades, the combination of hypervalent iodine reagents with gold, 91 and other transition-metals has allowed the functionalization of a broad range of substrates. 21 For example, the Hashmi group reported a bimetallic gold–silver catalytic system for the synthesis of 3-alkynyl benzofurans from phenols and EBx reagents ( Scheme 21 ). 92 Mechanistic studies, suggested that a bimetallic Au–Ag catalyst promoted a tandem ortho C(sp 2 )–H alkynylation/oxyalkynylation reaction by leveraging the exceptional redox property and carbophilic π-acidity of gold.…”
Section: Transition-metal Mediated Alkynylation Reactionsmentioning
confidence: 99%
“…10 Since the discovery of the exceptional reactivity of the hypervalent bond, hypervalent iodine reagents have attracted the interest of synthetic chemists. [13][14][15][16][17][18][19][20][21] In particular, alkynyl iodonium salts and ethynylbenziodoxolone (EBX) reagents have been particularly prolific as electrophilic alkyne synthons. [22][23][24][25] The peculiar reactivity of hypervalent iodine reagents arises from the 3-center-4-electron bond or hypervalent bond, which is longer, more polarized and weaker than a standard covalent bond leading to a higher electrophilic reactivity (Scheme 2A).…”
Section: Introduction and Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for iodine organic compounds has risen since then. Hypervalent iodine reagents are widely utilized as oxidants and electrophilic reagents in organic synthesis [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Hypervalent iodine reagents exhibit radical-type reactions, homolytic reactions, and singleelectron transfer (SET) reactions under the appropriate conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, construction of the C­(pyridyl)–N­(alicyclic) bond is of fundamental importance in synthetic and medicinal chemistry . In the C–N bond forming toolbox, direct heteroaryl C–H/N–H coupling should be an ideal adoption as it eliminates extra costly steps to prefunctionalize either coupling partner. , However, unlike the exceptionally broad arene (especially those with Py ring-contained DGs) , and five-membered heterocyclic substrates (Scheme a and b), C–H bond aminations of a free or fused Py ring with free amines (especially aliphatic amines) still remain underdeveloped because primary/secondary amines and Py rings have the tendency to adopt a nonproductive N-bound coordination mode with TMs, to result in a significant decrease of catalytic reactivity (Scheme c) . To this end, it is highly desirable to explore ideal C–H amination on a free or fused Py ring, wherein developing more reactive TM catalysis or installing easily removable DGs with weaker coordination capability on pyridyl-nitrogen atoms is a potential solution.…”
mentioning
confidence: 99%